The Influence of Project Based Creative Problem Solving Toward Creative Thinking Ability on Circulation System - Probowati, Desy; Iswari, Retno Sri; Sukaesih, Sri (FMIPA UNNES, 2020)
This study purposes to describe the influence the Project-Based Creative Problem Solving model in learning circulation system material toward students’ creative thinking. The study used One-Shot Case Study Design. Research subject is students of XI MIA 1 and XI MIA 3 classes as treatment groups. The independent variable of this research is Project-Based Creative Problem Solving learning model in circulation system material. The dependent variable is students’ creative thinking, activities and project result. The analysis result shows that the Creative Problem Solving Model Project-Base Circulation System Material has positive effect toward the students’ creative thinking by the percentage 86.1% for XI MIA1 and 91.66% for XI MIA3 with category very high. Analysis of reached indicator of creative thinking are fluent thinking/fluency 79.85% (high), flexible thinking/flexibility 91.15% (very high), original thinking/originality 77.35% (high), elaborate thinking/elaboration 89.2% (very high). The result of observations on students’ activity is more than 75% students gained good criteria. On the analysis of products result, mean of XI MIA 1 is 89.4% criteria good and 90.8% very good criteria for XI MIA 3. Base on the research result can be concluded that Creative Problem Solving Model Project Base Circulation System Material has very high positive influence toward students’ creative thinking in the circulation system material; students’ activity and projects’ result are very good also.